1986
DOI: 10.1002/ajmg.1320250215
|View full text |Cite
|
Sign up to set email alerts
|

Perception of consanguineous marriages and their genetic effects among a sample of couples from beirut

Abstract: We interviewed 100 women who had married a relative and 100 other women of the same age, religious affiliation, and socioeconomic status, but who were not related to their husbands. Both women were selected from a hospital setting in Beirut, and were questioned about their outlook on consanguineous marriages, their awareness of the genetic consequences of consanguinity, and their relationships with in-laws. In general, the women in consanguineous marriages were more favorably inclined than the matched women to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
3

Year Published

1989
1989
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 3 publications
1
31
0
3
Order By: Relevance
“…This would also lead to a higher probability of marriage between the offspring of two sisters, as a possible explanation for the excess of women among the intermediate ancestors, as well as for the excess of type II first-cousin matings in these pedigrees. An excess of female intermediate ancestors in close consanguineous matings, and the predominantly female role in the maintenance of family bonds has already been mentioned by Barrai et al [26](1962) in a study on Italian marriage records, and by Khlat et al [27](1986), with a different cultural background, among Muslims.…”
Section: Discussionmentioning
confidence: 83%
“…This would also lead to a higher probability of marriage between the offspring of two sisters, as a possible explanation for the excess of women among the intermediate ancestors, as well as for the excess of type II first-cousin matings in these pedigrees. An excess of female intermediate ancestors in close consanguineous matings, and the predominantly female role in the maintenance of family bonds has already been mentioned by Barrai et al [26](1962) in a study on Italian marriage records, and by Khlat et al [27](1986), with a different cultural background, among Muslims.…”
Section: Discussionmentioning
confidence: 83%
“…Studies in Saudi Arabia [16], Lebanon [17], and Israel (the Israeli Arab community) [4] have all found that families mainly approve of this type of marriage. Of particular interest is the observation within the Israeli Arab community that the opinions of those questioned about their attitudes towards consanguineous marriage reflected to a great extent their own situation, in that those whose own marriages were consanguineous were far more likely to be strongly encouraging of such a union, whereas those unrelated to their wives were more likely to object strongly [4].…”
Section: Social Aspects Of Consanguinitymentioning
confidence: 99%
“…The tendency in these societies of marrying relatives is a deeply rooted cultural trait (Hamamy 2011) related to ethnical, cultural, and socioeconomic factors (Khlat and Khoury 1991). Among Arab societies, it is believed that a consanguineous marriage preserves family structure and provides social, economic, and cultural benefits (Khlat et al 1986;Bittles 2008). These consanguineous marriages generally involve first or second cousins or relatives within the large family or the same tribe (Al-Khabory and Patton 2008).…”
Section: Introductionmentioning
confidence: 99%